2017
DOI: 10.3389/fpsyg.2017.00546
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Prenatal Parental Locus of Control on Children's Psychological Outcomes in Infancy and Early Childhood: A Prospective 5 Year Study

Abstract: Locus of control is one of the most widely studied concepts in the history of personality psychology. In spite of its popularity and its associations with numerous relevant outcomes, the ability of locus of control to predict future behaviors involving parenting effectiveness has been under researched. The few parent locus of control children's outcome studies are characterized by cross-sectional methodologies that focus on mothers. The present study uses a prospective methodology to compare data on mothers' a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
32
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 47 publications
(64 reference statements)
6
32
0
1
Order By: Relevance
“…Positive parent personality was associated with longer sleep durations and better sleep quality/daytime functioning. These findings are in line with prior research that has connected positive parent personality traits, such as internal locus of control, with positive health behaviours among children (Nowicki et al ., ). Sleep extension studies have found that even small extensions in sleep (e.g., ~30 min) are associated with better neurobehavioural functioning and improvements on cognitive tasks and working memory among children and adolescents (de Bruin, van Run, Staaks, & Meijer, ; Dewald‐Kaufmann, Oort, & Meijer, ; Sadeh, Gruber, & Raviv, ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Positive parent personality was associated with longer sleep durations and better sleep quality/daytime functioning. These findings are in line with prior research that has connected positive parent personality traits, such as internal locus of control, with positive health behaviours among children (Nowicki et al ., ). Sleep extension studies have found that even small extensions in sleep (e.g., ~30 min) are associated with better neurobehavioural functioning and improvements on cognitive tasks and working memory among children and adolescents (de Bruin, van Run, Staaks, & Meijer, ; Dewald‐Kaufmann, Oort, & Meijer, ; Sadeh, Gruber, & Raviv, ).…”
Section: Discussionmentioning
confidence: 97%
“…Parent attributes such as internal locus of control, hardiness, and optimism have been associated with positive child outcomes (Johnson & McMahon, 2008;McDonald, Kehler, & Tough, 2016;Nowicki, Iles-Caven, Gregory, Ellis, & Golding, 2017). For example, for toddlers with mothers with mental health problems, maternal optimism was a protective factor in the development of behavioural problems (McDonald et al, 2016).…”
Section: Promotive Factors and Positive Parent Personalitymentioning
confidence: 99%
“…Although there is a large body of evidence showing LoC to be associated with many psychological [2,3,5,6,33] and physical [7,8] health outcomes and health behaviours such as smoking [912] and alcohol consumption [9,17], studies examining whether LoC is related to cognitive function are scarce [22]. Several studies to date have assessed whether cognitive training is associated with short-term [18] and long-term [16] changes in LoC (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Parents' LoC is also important in the lives of children (Nowicki et al, 2017). LoC of parents and their children are significantly related with each other (Nowicki et al, 2018d).…”
Section: Global Social Sciences Review (Gssr)mentioning
confidence: 99%
“…Locus of control (LoC) is an important concept of personality (Nowicki et al, 2017). It is a person's perceived control on his or her life events.…”
Section: Introductionmentioning
confidence: 99%